2021
DOI: 10.1155/2021/6665028
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Metalloproteinase ADAM8 Is Upregulated in Liver Inflammation Models and Enhances Cytokine Release In Vitro

Abstract: Acute and chronic liver inflammation is driven by cytokine and chemokine release from various cell types in the liver. Here, we report that the induction of inflammatory mediators is associated with a yet undescribed upregulation of the metalloproteinase ADAM8 in different murine hepatitis models. We further show the importance of ADAM8 expression for the production of inflammatory mediators in cultured liver cells. As a model of acute inflammation, we investigated liver tissue from lipopolysaccharide- (LPS-) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Fifty‐nine out of 20,389 genes were differentially expressed in PMMA‐treated samples with 6 down‐regulated and 53 up‐regulated (see Figure 5A). Most of the up‐regulated genes (e.g., ADAM8, UPP1, SLC2A3) were related to pro‐inflammatory roles, the induction of migration of immune system cells, hypoxia processes, and inflammatory diseases 77–82 . For instance, the ADAM Metallopeptidase Domain 8 (ADAM8) is upregulated during inflammatory and allergic reactions 77,83 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifty‐nine out of 20,389 genes were differentially expressed in PMMA‐treated samples with 6 down‐regulated and 53 up‐regulated (see Figure 5A). Most of the up‐regulated genes (e.g., ADAM8, UPP1, SLC2A3) were related to pro‐inflammatory roles, the induction of migration of immune system cells, hypoxia processes, and inflammatory diseases 77–82 . For instance, the ADAM Metallopeptidase Domain 8 (ADAM8) is upregulated during inflammatory and allergic reactions 77,83 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the up‐regulated genes (e.g., ADAM8, UPP1, SLC2A3) were related to pro‐inflammatory roles, the induction of migration of immune system cells, hypoxia processes, and inflammatory diseases 77–82 . For instance, the ADAM Metallopeptidase Domain 8 (ADAM8) is upregulated during inflammatory and allergic reactions 77,83 . Similarly, the SLC2A3 gene (also known as GLUT3) is used as an important biomarker in the biological process of hypoxia and inflammatory diseases 79,81,82 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, we combined transcriptomic, proteomic, and ubiquitin-proteomic data from the positive regulation of cytokine production gene set for analysis, and we found 18 molecules that differed in multi-omics expression and that these molecules’ expression was mostly consistent in transcriptomics, proteomics, and ubiquitin-proteomics ( Fig 4E ). Among them, we found that the omic changes in ADAM8, ANXA1, SPTBN1, and STAT1 were highly correlated with inflammatory cell activation and cytokine production [ 47 51 ]. At the same time, we found significant expression of macrophage-associated inflammatory factors in both infected lung tissues and cells ( S5B and S5D Fig ).…”
Section: Resultsmentioning
confidence: 99%